Start up: A French program to support patients with pulmonary arterial hypertension during the adjustment of prostanoids to the individualized optimal dose - Emmanuel Bergot; Marie Fertin; Mélanie Gallant Dewavrin; Grégoire Prévot; Julia Meijer; Coralie Hakibilen; Laurette Gruand; Sophie Gauthier; Andreea Todea; Thamer Boukerzaza; Xavier Jaïs (PLoS ONE, 2025)
The Start Up program was initiated in patients with pulmonary arterial hypertension (PAH) with the objective to support them in taking their therapies targeting the prostacyclin pathway and determine the individualized optimal dose. This report focuses on selexipag, an oral prostacyclin receptor agonist that has been shown to delay the progression of PAH. Starting in 2016, patients who were prescribed selexipag for the treatment of PAH were offered participation in the Start Up program supported by the French PH network. During the dose adjustment phase, a nurse called the patients 3 days after drug initiation and after each dosage modification to provide support and to systematically grade and monitor adverse events (using Common Terminology Criteria for Adverse Events – CTCAE v4.0). The patients and the healthcare professionals rated their satisfaction with the program. Among the 406 patients who completed the program, 302 (74%) reached their individualized optimal dose for selexipag over a median period of 11 weeks. The reasons the individualized dose was not reached included treatment discontinuation (n = 78, 19%) and dropout for impaired communication skills (n = 8, 2%). Once the individualized optimal dose was reached, most patients had no, or mild (Grade 1) adverse events related to prostanoid use (49% and 45%, respectively). Both patients and healthcare professionals were satisfied with the Start Up program (scores of 9.1 ± 1.4 and 9.3 ± 0.7 on a 0–10 numerical scale, respectively). The proactive support and adverse event monitoring provided by the Start Up program during the early stages of treatment with selexipag was appreciated by patients and healthcare professionals and may contribute to improved compliance.